2021
DOI: 10.1007/s00572-021-01042-5
|View full text |Cite
|
Sign up to set email alerts
|

Ancient lineages of arbuscular mycorrhizal fungi provide little plant benefit

Abstract: Almost all land plants form symbiotic associations with arbuscular mycorrhizal fungi (AMF). Individual plants usually are colonized by a wide range of phylogenetically diverse AMF species. The impact that different AMF taxa have on plant growth is only partly understood. We screened 44 AMF isolates for their effect on growth promotion and nutrient uptake of leek plants (Allium porrum), including isolates that have not been tested previously. In particular, we aimed to test weather AMF lineages with an ancient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 96 publications
3
42
2
Order By: Relevance
“…For example, in a recent comparison of several AMF species belonging to different lineages, it was shown that two species (i.e. Archaeospora europaea and Paraglomus laccatum ) belonging to basal lineages did not provide nutritional benefits to leek (Säle et al ., 2021). Our meta‐analysis showed overall positive effects of basal lineages on plant performance, although in Poaceae they did not differ from zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent comparison of several AMF species belonging to different lineages, it was shown that two species (i.e. Archaeospora europaea and Paraglomus laccatum ) belonging to basal lineages did not provide nutritional benefits to leek (Säle et al ., 2021). Our meta‐analysis showed overall positive effects of basal lineages on plant performance, although in Poaceae they did not differ from zero.…”
Section: Discussionmentioning
confidence: 99%
“…As in Säle et al . (2021), to test the link between AMF taxonomy and mycorrhizal functioning, we followed Oehl et al . (2011) for clade names.…”
Section: Methodsmentioning
confidence: 99%
“…We reported the highest speciation rates in Glomeraceae and Diversisporaceae. Speciation rates in Paraglomeraceae and Archaeosporaceae, which are thought to be less beneficial for the plants than the fast diversifying Glomeraceae and Diversisporaceae (Säle et al, 2021), were an order of magnitude lower. We can therefore speculate that good symbiotic abilities may favor diversification, although this remains to be tested in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Diversisporaceae (Säle et al, 2021), were an order of magnitude lower. We can therefore speculate that good symbiotic abilities may favour diversification, although this remains to be tested in further investigations.…”
Section: Glomeromycotina Diversify Slowlymentioning
confidence: 91%